Changes in N-terminal pro-B-type natriuretic peptide and incidence of diabetes: The Multi-Ethnic Study of Atherosclerosis (MESA) - Sanchez, O.A. (Diabetes Metab, 2015)
AIMS: This study looked at whether the inverse association of circulating N-terminal pro-B-type natriuretic peptide (NT-proBNP) with incident diabetes is modified by changes in NT-proBNP (ΔNT-proBNP) levels. METHODS: lasma NT-proBNP was assayed at baseline and 3.2 years later (visit 3) in the Multi-Ethnic Study of Atherosclerosis (MESA).ΔNT-proBNP was calculated as NT-proBNP(visit3) − NT-proBNP(baseline). A Poisson distribution was fitted to determine the incidence density of diabetes, adjusted for age, race, gender, educational attainment, antihypertensive medication, total intentional exercise and plasma IL-6 levels. In the primary analysis (n = 3236 without diabetes up to visit 3, followed for a mean of 6.3 years), incidence density was regressed for the following categories of baseline NT-proBNP: (1) <54.4 pg/mL; (2) 54.4–85.9 pg/mL; and (3) 86–54.2 pg/mL. This was crossed with categories of ΔNT-proBNP as medians (ranges): (1) −6.2 (−131–11.7) pg/mL; (2) 19.8 (11.8–30.1) pg/mL; (3) 44.0 (30.2–67.9) pg/mL; and (4) 111.2 (68.0–3749.9) pg/mL. RESULTS: The incidence density of diabetes followed a U-shaped association across categories of ΔNT-proBNP within categories of baseline NT-proBNP after adjusting for other covariates (P = 0.02). At each level of baseline NT-proBNP, the incidence density of diabetes was lowest for small-to-moderate increases in NT-proBNP. CONCLUSION: This analysis suggests that NT-proBNP has a biphasic association with diabetes in which the risk of incident diabetes decreases within a ‘physiological range’ of ΔNT-proBNP, and plateaus or increases as NT-proBNP concentrations increase, probably in response to pathophysiological conditions leading to high levels of NT-proBNP.